Surveying the Expression of CDH1 and EGFR Genes in Patients with Anthracosis and Its Relationship with Lung Carcinoma - Zahra Izadian; Naghmeh Bahrami; Tahereh Naji; Abdolreza Mohamadnia (Asian Pacific Journal of Cancer Care, 2017)
Introduction: Anthracosis is known as the black lung disease and studies have shown relationships between the disease and lung carcinoma. In addition, the expression of CDH1 and EGFR genes can be used as the prognostic of anthracosis. The present study surveys the expression of CDH1 and EGFR genes in anthracosis patients and its relationship with non-small cells lung carcinoma. Methodology: Thirty anthracosis patients diagnosed by a specialist participated in the study. The subjects were asked to sign an informed letter of consent and then, to examine the expression of CDH1 and EGFR genes through real-time PCR, tissue samples were collected. Afterward, the relationship of expression of the biomarkers with tumor staging and cancer progress was examined. Results: Mean age of the patients was 48±10.5 years. As the reference gene, 18sRNA was adopted and comparison of mean CTs at the center and edges of lesions showed no significant difference. As to CDH1 gene at the center of lesions, 12 cases out of 30 were positive, which indicates 40% sensitivity; while at the edges, 20 cases out 30 were positive. Comparison of the positive rates of CDH1 gene at the center and edges of the lesions indicated a significant difference (P-value<0.001). Moreover and with regard to EGFR gene at the center of lesions, 19 cases out 30 were positive (sensitivity = 63.3%) and five cases out of 30 were positive at the edges of lesions (control). There was also a significant difference between the positive cases of EGFR gene at the center and edges of the lesions (P-value<0.001). Clearly, the positive cases of CDH1 at the edges were higher than that at the center, while in the case of EGFR gene, positive cases at the center were higher than that at the edges. It is notable that to obtan results with higher accuracy entails increasing the sensitivity level. Following similar studies and to have higher accuracy, the experiments were carried out with three iterations. Conclusion: In general, the results indicated a sort of relationship between anthracosis and lung carcinoma. To prove such relationship on a more solid ground, more studies with larger number of subjects are needed.